The groundwater flow regime of the Kombat Aquifer, Namibia - Mukendwa, Henry Mutafela (University of the Free State, 2009)
The Kombat Aquifer, as investigated in this study, comprises the dolomite of the upper and lower Otavi Group, encompassing a radius of about 10 km around Kombat Mine. Groundwater flow controls, structural influence, and hydraulic behavior of the groundwater flow system are investigated. The entire study area is initially conceptualized within a typical karst aquifer framework. Readily available data on climate, groundwater water levels, satellite geology, water chemistry, hydraulic tests, borehole hydrographs, borehole fracture logs, water strikes, geomorphology, supplemented with fracture field mapping and groundwater temperature logging, are used to delineate and study structures, structural controls, hydraulic response and to conceptualize the groundwater flow regime of the Kombat Aquifer. The results indicate that tectonic facies, layering, geomorphology, relief and relative position along the flow system largely influence the distribution of storage, permeability, hydraulic head stability, vertical and horizontal flow patterns, as well as the geometry of the Kombat Aquifer groundwater flow system. A comparison of groundwater temperature of the recharge and the discharge areas shows a temperature increase of about 5oC. An analysis of hydrograph recession curves enabled the understanding of the hydraulic response as well as the hydro_ dynamics of the flow system and confirmed the co-existence of two mutually inclusive groundwater flow components. The statistical examination of transport parameters reveals a very high tendency of dispersion, suggesting that extreme transport values could be more significant to groundwater flow parameterization than average values. A joint combination of blocky fracturing, flat relief and decreasing proximity to discharge zones enhance the long-term safe yield and hydraulic stability of production boreholes. Hence areas that are dominated by parallel fracturing, high elevation and long distances to discharge zones have the most unstable hydraulic head response and the lowest borehole yields. Results from hydraulic tests show that two permeability networks co-exist in different combinations and define the physical framework within which groundwater resides and moves. The connectivity between the two permeability networks characterise the hydraulic response of the Kombat Aquifer to groundwater withdrawal.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2009
Keywords: Groundwater -- Namibia; Aquifers -- Namibia; Groundwater flow; Hydrogeology -- Namibia; Kombat; Flow regime; Groundwater flow; Karst; Fractures; Faults; Structure; Aquifer